EFFECT OF THE PROBLEM BASED LEARNING MODEL WITH CONCEPT MAP ON PHYSICS STUDENTS ACHIEVEMENT - Rezky Amelia Putri; Gusnedi Gusnedi; Desnita Desnita; Wahyuni Satria Dewi (Department of Physics Universitas Negeri Padang, 2023)
One of the impacts of The Programme for International Student Assessment (PISA) on Indonesia is the change in the curriculum in the Indonesian education system. The curriculum that is implemented today, emphasizes students on 21st century skills and the change from teacher center to student center. The reality in the field, learning Physics in class shows that teachers still approach directly and involve students less in the learning process so that students are less motivated in learning which makes learning outcomes low. The purpose of this study was to see the effect of the problem based learning model with concept map on physics students achievement. This type of research is quasi experimental design. The instrument used in this study is a test instrument. The results showed that the average score of students in the experimental class of 63.88 was higher than the sample class of 59.21. Accompanied by quiz data, it also showed that the average score of the experimental class was higher than the control class at each meeting. The results of the hypothesis test obtained by the zcalculate >z table are 7.16>1.96 so that it can be said to reject Ho accept H1. Thus, the application of the PBL model accompanied by concept maps can be used and applied to students so that their learning outcomes increase